A study to assess the effect of pretreatment with intravenous palonosetron in preventing pain on propofol injection (Journal of Medical Science, 2023)
Background. Propofol is widely used for induction and maintenance of anaesthesia and possesses many characteristics of an ideal intravenous anaesthetic agent. It is known to cause severe, sharp, stinging, or burning pain on injection, which is considered unacceptable as it can cause agitation and interfere with the smooth induction of anaesthesia. In this study, we compare palonosetron and normal saline for decreasing pain on injection of propofol during intravenous induction of anaesthesia. Material and methods. One hundred adult patients belonging to ASA physical status I or II, scheduled for elective surgeries under general anaesthesia, were selected and randomly allocated to two groups. Group P received an injection of palonosetron, and Group S received an injection of regular saline as a pretreatment before the propofol injection. Patients were assessed for pain on propofol injection. Haemodynamic parameters and electrocardiography were recorded at the following points of time: prior to induction, after pretreatment, induction, and half-hourly during the surgery. Results. Comparing pain during propofol injection, 32% of the palonosetron group and 4% of the regular saline group did not experience pain; 54% of the palonosetron group and 20% of the regular saline group suffered mild pain; 12% of the palonosetron group and 48% of the regular saline group developed moderate pain; 2% of the palonosetron group and 28% of the regular saline group experienced severe pain. Conclusions. Pretreatment with palonosetron 0.075 mg reduced the incidence and severity of propofol-induced pain on injection, with the added advantage of decreased postoperative nausea and vomiting without significant haemodynamic changes.